International Alliances During The Cold War And Their Impact On The Global Level 1945-1991 - صلاط أيمن (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The European international system collapsed with the outbreak of World War II, which led to radical transformations and changes in the distribution of powers at the global level. The European countries, the “poles of the old order,” emerged from World War II exhausted economically, militarily, and politically. On the other hand, two new global poles emerged: the United States of America and Soviet Union. They are Under the new situation, the only ones capable of determining the image of the entire international system with the capabilities and capabilities they possess. The dispute between the two poles had a significant impact on the emergence of a new variable that played a fundamental role in the international conflict, which is the ideological factor. This dispute led to the division of the countries of the world into two main blocs: the Western “capitalist” bloc, led by the United States of America, and behind it the countries of Western Europe, Canada, and Japan. And the socialist “communist” bloc, led by the Soviet Union and its successors, the countries of Eastern Europe. These two blocs are represented by both NATO and the Warsaw Pact. In their conflict with each other on the territory of the Third World, both poles resorted to indirect means to avoid direct armed conflict between them. Examples of these means include (diplomacy, economic propaganda, establishing alliances, supporting loyal regimes, and working to overthrow hostile regimes), all of which resulted in what It was called the "Cold War."